2019
DOI: 10.30848/pjb2019-4(21)
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physio-biochemical indicators for drought tolerance in different cultivars of maize (Zea mays L.)

Abstract: Maize is an important cereal crop all-over the world and has been recently ranked at first among all cereal crops. However, growth of maize plants is negatively affected in arid and semi-arid areas of the globe due to scarcity of water, but genetically variable cultivars/lines differ considerably to respond to water limited conditions. To evaluate the response of some commercial cultivars of maize to water deficit conditions, a pot experiment was carried out. Eight maize cultivars (Sultan, Akbar, Pearl, MMRI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…However, the present study was carried-out to assess the effectiveness of exogenously applied L-methionine in upregulation of growth and some key biochemical processes of sunflower ( Helianthus annuus L.) plants exposed to water-deficit stress. It is now well evident that drought stress can markedly suppress the growth of plants, as already observed in different crops e.g., carrot [ 56 ], radish [ 57 ], maize [ 58 ], sunflower [ 59 ], and mung bean [ 60 ]. In the present study, drought stress (60% F.C.)…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study was carried-out to assess the effectiveness of exogenously applied L-methionine in upregulation of growth and some key biochemical processes of sunflower ( Helianthus annuus L.) plants exposed to water-deficit stress. It is now well evident that drought stress can markedly suppress the growth of plants, as already observed in different crops e.g., carrot [ 56 ], radish [ 57 ], maize [ 58 ], sunflower [ 59 ], and mung bean [ 60 ]. In the present study, drought stress (60% F.C.)…”
Section: Discussionmentioning
confidence: 99%
“…However, the drought tolerance characteristic of crops is probably the most difficult to identify with great precision, since grain yield is a complex trait and is influenced by the genotype by environment interaction and other mechanisms associated with heterosis (Pereira 2016). Thus, in the absence of precise information regarding the complete genetic mechanism of drought tolerance in maize, some secondary characteristics of the plant have been used as selection criteria, such as agronomic traits and molecular markers (Mikić et al 2016), morpho-physiological mechanisms (Wattoo et al 2018), and physiobiochemical indicators (Shafiq et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To attain optimum growth and yield production, plants require both water and nutrients in the proper amount to fulfill their basic needs. Under water‐limited conditions, a significant reduction in plant growth and yield production has been observed in different crops, for example, canola (Shafiq et al 2014), cauliflower (Latif et al 2016), maize (Shafiq et al 2018), sunflower (Kosar et al 2018) and mungbean (Sadiq et al 2019). In all these studies, it has been reported that water stress‐induced reduction in plant growth can be related to oxidative stress, nutritional imbalance, hormonal alterations, suppression/deterioration of proteins, deactivation of enzymes and disturbance in secondary metabolism.…”
Section: Discussionmentioning
confidence: 99%